The spatial and temporal patterns of declared personal income across Greece: 2001-8 - Prodromos Prodromidis (European Regional Science Association (ERSA), 2012)
The paper studies the income mosaic of Greece at the local community level, from the time the country joined the EMU to time the international crisis reached its shores. It econometrically isolates the impact of past average income and the size of income-filing population, as well as the annual effects; and tries to explain in terms of demographic, educational, and other attributes of the population, as well as geographic features, the number of times (years) that local income exceed the level predicted. To the extent the residuals are produced by unknown (missing) variables, their sub-regional and cross-regional patterns offer clues in the direction of formulating better, spatially targeted interventions. There is a real need for policy suggestions that stretch the funds permitted by the fiscal straitjacket to go further in pulling the country out of the recession. Overall, the paper provides a better understanding of the internal heterogeneity of Greece, the sub-national operation of the economy, and the generation and distribution of personal income.
Keywords: C23; D31; R12; 330; personal income; disaggregated data; extracting information from the residuals; delineation of micro-regional policy areas; urban and rural development